Efectos de la presencia de bullyng en la convivencia pre - escolar en los infantes de 5 años pertenecientes al jardín "mi mundo de diversión", beneficiarios de la ong ama perú, en el distrito de moche, año 2014. - Rodriguez Espejo, Pilar Milagros (2015)
This descriptive research was carried out in order to know the effects that the presence of Bullying in pre-school life in infants 5 years belonging to Garden My World of Fun, Love NGO beneficiaries of Peru Nonprofit Organization, in the district of Moche during 2014.La sample consisted of 16 infants, which was selected through simple random sampling. This research is divided into two parts, the first discloses the problematic reality of this present study highlighting the theme of bullying, also the background as the theoretical and conceptual framework. Similarly also highlights the problem statement, by the hypothesis of the research objectives and finally the methodology. In the second part the results, which is divided into chapters is; Chapter I disclosed gender, origin, religious affiliation and likewise the family type of infants; On chapter II, we find data on the occurrence of bullying, which discloses the type of involvement in bullying, the situations witnessed by spectators, just as the situations experienced by the victims, as well as the situations made by the aggressors and finally the type of aggression; On chapter III we find the data on the effects of bullying, which gives references to the type of interpersonal relationships, as well as the kind of teamwork, the kind of attitude and development outside the school, just as the kind of emotional state also the type of sleep disturbance and finally the type of fitness. At the end of this research in mind the discussion of findings, conclusions and recommendations thereof, references and finally the annexes to this investigation.